2023
DOI: 10.1007/s00167-023-07527-4
|View full text |Cite
|
Sign up to set email alerts
|

Tibial bone defect prediction based on preoperative artefact‐reduced CT imaging is superior to standard radiograph assessment

Marco Brenneis,
Dimitrios A. Flevas,
Troy D. Bornes
et al.

Abstract: Purpose The purpose of this study was to evaluate the accuracy of preoperative CT-based Anderson Orthopaedic Research Institute (AORI)-grading and to correlate Computed tomography (CT)-based volumetric defect measurements with intraoperative AORI findings. Methods 99 patients undergoing revision total knee arthroplasty (rTKA) with preoperative CT-images were identified in an institutional revision registry. CT-image segmentation with 3D-Slicer Software was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This should be considered especially in younger patients, as the likelihood of radiation-induced malignancy is a function of the patients' age [23]. Nevertheless, previous studies reported a low sensitivity of X-ray in detecting osteolytic lesions around TKA implants (0% small defects [mean 0.7 cm³] -66% large defects [mean 3.5 cm³]) and only fair agreements between preoperative X-ray assessments and intraoperative grading (κ value of 0.304), highlighting the need for improvement of preoperative assessment [4,10,14]. This indicates that while X-rays may offer some preliminary insights, CT scans and the 3D-segmentations are more precise and offer the potential to assist in predicting the sizes of cones and sleeves that may be required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This should be considered especially in younger patients, as the likelihood of radiation-induced malignancy is a function of the patients' age [23]. Nevertheless, previous studies reported a low sensitivity of X-ray in detecting osteolytic lesions around TKA implants (0% small defects [mean 0.7 cm³] -66% large defects [mean 3.5 cm³]) and only fair agreements between preoperative X-ray assessments and intraoperative grading (κ value of 0.304), highlighting the need for improvement of preoperative assessment [4,10,14]. This indicates that while X-rays may offer some preliminary insights, CT scans and the 3D-segmentations are more precise and offer the potential to assist in predicting the sizes of cones and sleeves that may be required.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ratio of remaining tibial bone volume (bone volume minus total defect) to the total tibial bone was computed to allow comparison across bones of different sizes. This 3D segmentation method used in the current paper has been validated by comparing CT defect measurements to intraoperative surgeon assessment [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation